With Frenemies Like These: Rising Power Voting Behavior in the UN General Assembly. Issue 1 (8th January 2022) - Binder, Martin; Lockwood Payton, Autumn
Abstract: The rise of non-Western powers has led to competing claims about how these states act among each other and how they behave vis-à-vis established powers. Existing accounts argue that the rising powers are a heterogenous group of competing states and that they are socialized into the existing Western-centered order. This article challenges these claims, arguing that the rising powers are dissatisfied with the international status quo and that they have begun to form a bloc against the established powers. The authors contend that this dissatisfaction arises from their lack of influence on the international stage, their status in the international hierarchy and the norms that sustain the current international order. They maintain that the formation of a rising powers bloc is driven by the countries' economic growth and international dynamics, fostering their institutionalization as IBSA (India, Brazil, South Africa) and BRICS (Brazil, Russia, India, China, South Africa). To support this argument, the study combines spatial modeling techniques to analyze rising power voting behavior in the UN General Assembly over the period 1992–2011.